A New Modulation Technique to Improve Received Power Under Turbulence Effects For Free Space Optical Communication - A. K., Rahman; A L, Tom; Nur Alia Athirah, Mohtadzar; Yonis M Yonis, Buswig; Nurdiani, Zamhari; Dyg Norkhairunnisa, Abang Zaidel; Siti Kudnie, Sahari; Norhuzaimin, Julai (IOP Publishing Ltd, 2019)
This paper focus on new modulation technique to improve the performance of the conventional modulation that uses intensity modulation/direct detection (IM/DD) for On-Off Keying (OOK) modulation. This new modulation technique that is Dual Diffuser Modulation (DDM) can create superior modulation with able to reduce scintillation index, enhance power received and threshold signal level. The analysis result shows that the free space optical (FSO) can have good performance of power received under strong turbulence. The DDM are better performance as compare with conventional IM/DD-OOK and IM/DD-OOK with diffuser. This can help FSO system to combat with severe turbulence effect for optimum operation.